PENDAFTARAN DAN VERIFIKASI KEANGGOTAAN PARTAI POLITIK CALON PESERTA PEMILIHAN UMUM TAHUN 2024 DI KOTA PONTIANAK - NIM: A1011201178, RAHMADINA WARDANTI (Fakultas Hukum Universitas Tanjungpura, 2024)
ABSTRACT In this thesis, the author raises the important issue of the registration and verification of membership of political parties and candidates for the 2024 General Election in Pontianak City. This research aims to analyze the phenomenon of election malpractice that occurs in the registration and verification of membership of Political Parties as candidates for the 2024 General Election in Pontianak City, and to identidy ways the efforts to handle it in following up on election malpractice as personal data protection.In this thesis, researchers employed qualitative research methods with an empirical approach and legal research. The type of data in this thesis comprises of primary data obtained through direct interviews to obtain information and secondary data obtained through literature studies and from literature both print and electronic. Based on the research conducted by the researchers, the results and conclusions obtained are that in the use of electoral technology such as SIPOL there are still problems found that show anomalies (irregularities). Electoral malpractice in the registration and verification of membership of political parties as candidates for the 2024 general election in Pontianak city occurs due to: 1) Failure of political parties as candidates for the general election in aspects of Law No. 7 of 2017 on Elections and PKPU No. 4 of 2022 on Registration, Verification and Determination of Political Parties Participating in the General Election of Members of the House of Representatives (DPR) and Regional House of Representatives (DPRD), which has been amended as a result of the implementation of Constitutional Court Decision No. 55/PUU-XVIII/2020; 2) The lack of transparency in the recruitment of political parties in carrying out political recruitment functions; and 3) The public awareness and knowledge of the urgency of personal data protection is still low. The handling efforts made in following up on the phenomenon of electoral malpractice are to clarify the suggestions for improving the requirements of political party documents and deleting individuals' personal data from the membership lists of political parties in SIPOL in accordance with Article 57 of Law Number 27 of 2022 concerning Personal Data Protection. Keywords: Registration and Verification, Electoral Integrity, Political Parties, Electoral Malpractice, Human Rights ABSTRAK Pada skripsi ini, penulis mengangkat permasalahan Pendaftaran dan Verifikasi Keanggotaan Partai Politik Calon Peserta Pemilihan Umum Tahun 2024 di Kota Pontianak. Penelitian ini bertujuan untuk menganalisis fenomena malapraktik Pemilu yang terjadi dalam pendaftaran dan verifikasi keanggotaan Partai Politik calon peserta Pemilihan Umum tahun 2024 di Kota Pontianak, dan mengetahui upaya penanganannya dalam menindaklanjuti malapraktik Pemilu sebagai perlindungan data pribadi.Dalam skripsi ini peneliti menggunakan metode penelitian kualitatif dengan pendekatan empiris maupun riset hukum yuridis. Jenis data pada skripsi ini terdiri dari data primer yang diperoleh dengan wawancara secara langsung untuk memperoleh informasi dan data sekunder didapatkan melalui studi kepustakaan dan dari literature. Berdasarkan penelitian yang peneliti lakukan, diperoleh hasil dan kesimpulan bahwa dalam pemanfaatan teknologi kepemiluan semacam SIPOL masih terdapat permasalahan-permasalahan yang ditemukan yang menunjukkan ketidaknormalan (irregulitas). Malapraktik Pemilu pada pendaftaran dan verifikasi keanggotaan Partai Politik calon peserta Pemilihan Umum tahun 2024 di Kota Pontianak terjadi diantaranya karena: 1) ketidakpatuhan Partai Politik calon peserta Pemilu dalam aspek Undang-Undang Nomor 7 Tahun 2017 tentang Pemilu dan PKPU Nomor 4 Tahun 2022 tentang Pendaftaran, Verifikasi, dan Penetapan Partai Politik Peserta Pemilihan Umum Anggota Dewan Perwakilan Rakyat (DPR) dan Dewan Perwakilan Rakyat Daerah (DPRD) yang mengalami perubahan sebagai konsekuensi pemberlakuan Putusan MK Nomor 55/PUU-XVIII/2020; 2) kurangnya keterbukaan pada rekrutmen Partai Politik dalam menjalankan fungsi rekrutmen politik; dan 3) kesadaran dan pengetahuan masyarakat terkait urgensi perlindungan data pribadi yang masih minim. Adapun upaya penanganan yang dilakukan dalam menindaklanjuti fenomena malapraktik Pemilu dengan melakukan klarifikasi untuk saran perbaikan dokumen persyaratan Partai Politik dan penghapusan data pribadi masyarakat dalam daftar keanggotaan Partai Politik pada SIPOL sebagaimana telah sesuai pada Pasal 57 Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi. Kata kunci: Pendaftaran dan Verifikasi, Pemilu berinteritas, Partai Politik, Malapraktik Pemilu, Hak Asasi Manusia